Cross sectional study of exhaled nitric oxide levels following lung transplantation. Issue 6 (1st June 1998) - Fisher, A J; Gabbay, E; Small, T; Doig, S; Dark, J H; Corris, P A
Abstract : BACKGROUND: The role of nitric oxide (NO) in the pathophysiology of graft dysfunction following lung transplantation remains unclear. To determine whether measurement of NO in the exhaled breath of lung transplant recipients provides useful information about graft pathology, a cross sectional study was performed on a cohort of recipients as they attended for review. METHODS: One hundred and four lung transplant recipients and 55 healthy non-smoking controls were included in the study. Each subject performed three consecutive single breath NO manoeuvres. In recipients NO levels were compared according to current clinical status, presence of any graft pathology, type of lung transplant procedure, indication for transplantation, and current level of immunosuppression. RESULTS: Mean (SE) exhaled NO levels were 6.5 (0.61) ppb in the control group, 5.3 (0.46) in clinically well recipients, 10.3 (1.4) in those with lymphocytic bronchiolitis, 10.5 (1.0) in recipients with infection, and 2.5 (0.6) in those with acute vascular rejection. There was no significant difference in NO levels between the control group and lung transplant recipients as a whole (mean difference 0.29 (95% CI –1.17 to 1.75), p = 0.7). Levels were increased significantly in the presence of lymphocytic bronchiolitis (4.98 (95% CI 1.6 to 8.36), p = 0.0002) and infection (5.28 (95% CI 2.9 to 7.56), p<0.0001), but not in acute vascular rejection (2.76 (95% CI 0.97 to 4.55), p = 0.1) compared with exhaled NO in clinically well recipients. Recipients with obliterative bronchiolitis were subdivided according to the grade of their bronchiolitis obliterans syndrome (BOS). Exhaled NO levels in those with BOS grade 1 were 10.0 (1.3) ppb and in those with BOS grades 2 or 3 were 5.1 (0.7) ppb. Compared with those who were clinically well, NO levels were increased in those with BOS grade 1 (4.74 (95% CI 1.8 to 7.69), p < 0.0001) but not in those with BOS grades 2 or 3 (0.19 (95% CI –1.55 to 1.93), p = 0.82). CONCLUSIONS: Exhaled NO levels are increased in lung transplant recipients with lymphocytic bronchiolitis, early obliterative bronchiolitis, and infection. These conditions are all associated with the presence of airway inflammation within the graft. The findings suggest that exhaled NO measurements may have a role as a marker of pulmonary allograft dysfunction.